Implementation of 100% Electric Vehicle in Bali with the Supply of Potential Independent Solar Energy - Zensu, Sudarno; Dalimi, Rinaldy (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2022)
Electrical vehicle is the future of transportation. This thesis is about how to transform the usage of fossil fuel vehicle to electrical vehicle in Bali. Bali is an island with the longest distance from one of its districts to Denpasar city is 95,6 km. This distance is reachable by the common electrical vehicle that available in the market now. The usage of the electrical vehicle requires good development and planning, otherwise it will cause problem for the electrical systems. The consumption of electrical energy will increase.Â In 2019, Bali used 5,908 GWh electricity in a year. And if all the 2 wheels and 4-wheels vehicles now are electrical vehicle, it will require extra 2,823 GWh per year. It will impact the planning of power generation in Bali.Another challenge for the electrical systems is the duck curve problem. The habit of the user charges their vehicle will also impact the daily load curve of an electrical systems. If all the two wheels and four wheels vehicles now are electrical vehicle, and allÂ Â users conduct the charging at the same time in 4 hours duration, the load will increase about 1,934 GW. The practical and applicable solution is the independent power producer concept by the solar PV. If every electric vehicle user installs the solar PV for their electrical vehicle consumption, this will solve all the problem.